2008
DOI: 10.1007/s00011-007-7213-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolarity causes inflammation through the methylation of protein phosphatase 2A

Abstract: Hyperosmolarity can induce pro-inflammatory cytokine responses in colorectal and bladder epithelial cells. Inflammation appears to be the simple consequence of a shift of methylation of PP2A which in turn activates NF-kappaB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 56 publications
3
55
0
Order By: Relevance
“…Similarly to hyperosmotic shock (2,29), the toxicity of carbon dioxide is partly mediated by the activation of PP2A, which results in the translocation of NF-B. The mechanism of action of CO 2 might also involve the inhibition of the Krebs cycle and glycolysis for stoichiometric reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to hyperosmotic shock (2,29), the toxicity of carbon dioxide is partly mediated by the activation of PP2A, which results in the translocation of NF-B. The mechanism of action of CO 2 might also involve the inhibition of the Krebs cycle and glycolysis for stoichiometric reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine secretions into the supernatants of HT-29 and A549 human cells (cultivated in 25-cm 2 flask) were quantified after a 48-h culture using the DuoSet ELISA development kit (R&D Systems, Minneapolis, MN) for human IL-8, IL-6, and MCP-1, as already described (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as there is now considerable ONCOLOGY REPORTS 23: 1407-1416, 2010 A combination of alpha lipoic acid and calcium hydroxycitrate is efficient against mouse cancer models: Preliminary results interest in the role of the glycolytic phenotype as a key target for the development of effective drugs for cancer, the inflammatory response has also been recognized as a potential target (12,13). Our laboratory has in the past few years investigated the role of hyperosmolarity as a cause of inflammation and its potential link to cancer (14)(15)(16) and most recently showed that the inhalation of carbon dioxide, a product of cellular respiration, was able to induce inflammation of the lung (17). As a consequence, focusing on metabolic changes involving glucose metabolism that characterize cancer cells appeared to us to be a logical extension of our work in the area of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research and application history in Germany -Promotion of endogenous fat mobilization and oxidation [7] -Studies as an antiulcer agent [10] -Resuscitation from diabetic coma (early Japanese and German observations) -Prevention of adrenocortical suppression during steroid therapy [7] -Increase in auditory threshold values in patients with Ménière's disease [11,12] -Therapy of adenosine deaminase deficiency in a form of adult myopathy [13] -Therapy of glucose 6-phosphate dehydrogenase deficiency in red blood cells (anemia) [14] -Restoration of heart muscle adenine nucleotide levels [15] -Increase in the levels of retinol-binding proteins [7] -Reduction in the incidence of liver and bile duct disorders [7]; older literature shown in ref. [21] -Amelioration of drug-induced hemolysis [22] -Prevention of acute middle ear infections in infants [23][24][25] -Antibacterial effect on pneumococcal nasal colonization [26] -Alleviation of cystic fibrosis condition [27] -Stimulation of cytokine induction (rat bladder cell lines) [28] -Reconstitution of integral membrane transport proteins [29] -Skin care with farnesol (atopic dry skin; Staphylococcus aureus)…”
Section: The Chemical Profile Of Alditolsmentioning
confidence: 99%